E-Money ad Inflation on Indonesa's Economic Growth - vannita; Yonson Pane (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
In the context of Industry 4.0, where digital technologies are becoming increasingly prevalent, the utilization of e-money as a technological innovation in financial transactions offers a convenient and efficient solution that has the potential to enhance the efficiency of the payment system and facilitate the collection of taxes. The objective of this study is to examine the impact of the utilization of e-money and inflation on economic growth in Indonesia. Using a quantitative method with secondary data x1 and x2 using data sourced from Bank Indonesia (BI) and y using data from the BPS, also known as Statistic Indonesia. The sampling technique used is a total sampling technique or census using the entire population as a sample from 2013-2023 with quarterly data (4 x 11 = 44). Data testing was carried out with descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The results of the study show that the X1 variable has a partially significant effect on economic growth with a -T value of -2.531 < -T table -2.0227. The X2 variable shows a T value of 3.056 > T table 2.0227, which means that inflation has a significant influence on economic growth. The results of the simultaneous test on the variables of e-money and inflation on economic growth showed that the F value was calculated at 11.573 > the F value of table 3.24, which means that e-Money transactions and inflation had a simultaneous effect on economic growth.